Backhaul Effect on User Association in cellular and WiFi Networks - Ahmed I. Abdulshakoor; Mahmoud M. Elmesalawy; Gamal A. Khalaf (International Telecommunications Society (ITS), 2019)
The huge growth of data traffic has led to a continuous increase in capacity demands in mobile networks. A cost effective approach is to offload data traffic to WiFi network for enhancing the network capacity and improving the system performance. In this paper, we study the effect of the network backhaul on the selection decision for this network. We are dealing with a single and multi-hop wireless backhaul transmission under different circumstances and different numbers of associated users. One of MADM algorithms which is widely adopted is Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). We use TOPSIS in order to arrange the available networks, according to several metrics and based on the user priorities and requirements. Thus helping for optimum user-network association that will improve the system performance while satisfying the user requirements. The analytical results show the importance of taking the backhaul effect during the user association process and how the backhaul link effects the overall performance.
Keywords: 330; Backhaul; WMN; Cellular network; backhaul delay